The development of international accounting and auditing standards for fair value accounting in the Arab Middle East, Jordan: a systematic review - Alharasis, Esraa Esam; Prokofieva, Maria; Clark, Colin; Haddad, Hossam; Alramahi, Nidal (Cogent business & management, 2024)
A comprehensive literature review and analysis of auditing and "fair value accounting (FVA)" growth in Jordan and the "Arab - Middle Eastern (ME)" region are presented in this paper. It determines fair value implementation criteria and their impact on auditing pricing and application status. This paper reviewed relevant academic literature extensively. We used PRISMA principles to formulate questions and use systematic and explicit methods to identify, select, and critically evaluate relevant papers. More than 155 top accounting journal papers from 2000 to 2023 are reviewed. Qualitative content analysis of FVA literature revealed two main themes. The first theme, institutional factors on FVA application decisions in the region, has three main topics: theoretical underpinning, local factors, and accounting system heritage. The second theme is FVA’s effects on auditing. The first theme found that institutional isomorphism drives FVA practices in Jordan, and the second theme shows that complex asset and liability estimates make FVA application difficult in Jordan. This review is the first to examine FVA and auditing. The identified subjects and subtopics’ theoretical underpinning and practical applicability are reviewed. The analysis concludes with research recommendations and limitations.